FORMING OF FARM ACTIVITIES IN UZBEKISTAN - Sanjarbek Khamrajonovich Mamajonov (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides a scientific analysis of the establishment of farms in the Republic of Uzbekistan during the years of independence, the reforms implemented by the government in the first and second stages of its development and their results on the basis of literature and archival sources.